Panorama urbano de los Equipamientos de Educación Superior (EES) en la ciudad de Bogotá (2009)
The present article deepens in the general urban panorama of the university equipment in the city of Bogotá, with the purpose of establishing possible territorial structures for the future conformation of a system of university equipment. The objective of this article is centered in making a territorial x-ray as a way to diagnose localization, covering, functional relationships, relation to general systems, etc., of the university equipment in the year 2006, with the purpose of establishing the conceptual and territorial bases that would be the starting point to recommend a system of university equipment on the light of the Master Plan of Education, defined by the Plan of Territorial Ordinance of the city of Bogotá